1999
DOI: 10.1103/physreve.60.1299
|View full text |Cite
|
Sign up to set email alerts
|

Power-law distributions and Lévy-stable intermittent fluctuations in stochastic systems of many autocatalytic elements

Abstract: A generic model of stochastic autocatalytic dynamics with many degrees of freedom wi, i = 1, . . . , N is studied using computer simulations. The time evolution of the wi's combines a random multiplicative dynamics wi(t + 1) = λwi(t) at the individual level with a global coupling through a constraint which does not allow the wi's to fall below a lower cutoff given by c ·w, wherew is their momentary average and 0 < c < 1 is a constant. The dynamic variables wi are found to exhibit a power-law distribution of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 24 publications
(37 reference statements)
2
63
0
Order By: Relevance
“…(29), and the ex- This provides an effective lower cutoff for the range of x in which a power-law behavior is observed. This result can be compared to a somewhat simpler model studied earlier, in which the value of the lower cutoff x min is imposed as a constraint [15]. In this model, using the sum rules for the probability and the total wealth, it was found that x min = 1 − 1/α.…”
Section: Numerical Simulations and Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…(29), and the ex- This provides an effective lower cutoff for the range of x in which a power-law behavior is observed. This result can be compared to a somewhat simpler model studied earlier, in which the value of the lower cutoff x min is imposed as a constraint [15]. In this model, using the sum rules for the probability and the total wealth, it was found that x min = 1 − 1/α.…”
Section: Numerical Simulations and Resultsmentioning
confidence: 97%
“…. , w n , t) ≡ 0, wherew(t) does not reach a steady state and diverges to infinity (for λ > 0) or collapses to 0 (for λ < 0) [15]. This can lead to changes by orders of magnitude in the total wealth or the population size without affecting the exponent α.…”
Section: Numerical Simulations and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For low to medium income it has a functional form that has been variously described as exponential or log-normal [102,103], but for very high incomes it is better approximated by a power law. Since the early efforts of Champernowne, Simon, and others, the most successful theories for explaining this have been random process models for the acquisition and transfer of wealth [102,[104][105][106][107][108]. If these theories are right, then the distribution of wealth, which is one of the most remarkable and persistent properties of the economy, has little to do with the principles of equilibrium theory, and indeed little to do with human cognition.…”
Section: Distribution Of Wealth and Firm Sizementioning
confidence: 99%